Incidencia de los dibujos animados de televisión en el aprendizaje sociocognitivo de los niños/as de primaria - Moral Pérez, Maria Esther del (Revista Española de Pedagogía, 2018)
We analize the influence of cartoons passed on T.V. in the sociocognitive learning development in Primary Education, as a potencially educational factor. The phenomenon of cognitive schemas building up, general children¿s development, the social integration process in chilhood at early stages, and TV- learning interaction, are also studied. Finally, TV and mainly cartoons programmnes are questioned as important learning elements; their possible cognitive and affective effects are also studied
Keywords: dibujos animados; televisión; aprendizaje sociocognitivo; niños; primaria; Revista Española de Pedagogía